Atenção integral ao portador da síndrome do olho seco grave pelo SUS: um estudo exploratório - Almeida, Cleivania Lima de [UNIFESP] (2017)
Objective: Describing the paths covered by the Dry Eye Syndrome patient in search of the integral attention of health care by the Unified Health System (SUS). The object of study was constructed from the contextualization of the disease in the world scenario, including in Brazil, the understanding of the disease as a public health problem, as well as from the point of view of systemic integrality, through public policies, and the integral attention of individual health care, including psychosocial aspects. Method: This is a research with a qualitative and exploratory approach that involved two stages: the theoretical-conceptual and the empirical. In the first one, papers which approach the theme of this study were used, including a bibliographical research corresponding to the period of 2011-2015. In the second stage, the tools used were the observance of focal groups and semi-structured interviews, and as support, the field diary. The focal groups, with the participation of users of the Outpatient Clinic of External Diseases and Cornea, with Dry Eye Syndrome, in order to know the paths covered in the search for integral care. The final sample for the analysis consisted of 14 participants. The semi-structured interviews with managers of the Department of Ophthalmology to know the dynamics of the functioning of the services, including psychosocial assistance, and the ophthalmologist, regarding the assistance to the bearer of Dry Eye Syndrome by the service studied. The field diary was the instrument used to register the recognition of the research scenario, as well as other events during the study, including during focus groups and semi-structured interviews. This study was carried out in a university service linked to the Department of Ophthalmology of a Medical School linked to a Federal University. Results: Regarding the empirical analysis, it can be affirmed that health care for patients with Dry Eye Syndrome falls short of the principle of integrality. In both management and care, the Unified Health System has gaps that affect the quality of life of people suffering from the disease. Considerations: Finally, this study proposes some actions aiming at making the SUS more accessible to the bearer of Dry Eye Syndrome, including suggesting the approach of the Department of Ophthalmology with the basic network, the integration between psychology / psychotherapy services, social care and clinical-surgical ophthalmology, and, in the service studied, the stimulus for the formation of a support group with patients with the disease in partnership with the Association of Carriers of Dry Eye, an entity considered as the spokesperson for those who suffer from this disease to the Brazilian population, through its actions.